A Meta-Synthesis Study of Forelearn Apperception Process: Strategy to Overcome Jetlag Issues in Early Learning Activities - Tristan Rokhmawan; Lailatul Fitriyah; Ahmad Fikri Ab Rahmani; May Dwi Rokhmawati; Mukharomah Mukharomah (Bulletin of Pedagogical Research, 2023)
This study offers a metasynthesis analysis of Forelearn Apperception strategies, shedding light on their diverse applications in educational contexts. With a focus on the jetlag issue between regional Indonesian and international journal publications, this research delves into the nuances of strategies deployed by educators to integrate aperception into instructional practices. Methodologically, this research employed metasynthesis to extract and analyze data from a range of sources. By synthesizing insights from various studies, a comprehensive understanding of the multifaceted aspects of Forelearn Apperception strategies was achieved. The analysis also unveiled a progression in strategy emphasis across educational levels, from enthusiasm generation in early education to the development of critical thinking and problem-solving skills in higher education. The findings underscore the dynamic nature of educational practices, with strategies adapted to cater to the cognitive development and educational levels of students. The application of diverse aperception approaches emerges as pivotal in creating an engaging learning environment. The study substantiates its conclusions with theoretical underpinnings such as Constructivist Learning and Intrinsic Motivation theories. In conclusion, this metasynthesis analysis provides valuable insights into the versatile utilization of Forelearn Apperception strategies in diverse educational settings. By integrating these strategies, educators can nurture engaging learning experiences, deeper comprehension, and lifelong learning skills while addressing the multifaceted jetlag issue. Keywords: Forelearn Apperception, Metasynthesis Study, Jetlag Issue Early Learning